2014
DOI: 10.1080/10494820.2014.979208
|View full text |Cite
|
Sign up to set email alerts
|

A time sequence-oriented concept map approach to developing educational computer games for history courses

Abstract: Concept maps have been recognized as an effective tool for students to organize their knowledge; however, in history courses, it is important for students to learn and organize historical events according to the time of their occurrence. Therefore, in this study, a time sequence-oriented concept map approach is proposed for developing a game-based environment to facilitate students' learning of historical events and their organization during the gaming process. With this approach, students can easily learn the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
13
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 12 publications
(13 citation statements)
references
References 52 publications
0
13
0
Order By: Relevance
“…Knowledge mapping has the advantage of providing students concrete content through explicit knowledge graphics (Ebener et al 2006). Previous studies have shown that the incorporation of knowledge structures into educational games could effectively enhance students' achievement without affecting their motivation and self-efficacy (Chu et al 2015). For this reason, this study attempted to visualize the structure of knowledge in an educational game.…”
Section: Digital Educational Games For Mathematics Learningmentioning
confidence: 99%
“…Knowledge mapping has the advantage of providing students concrete content through explicit knowledge graphics (Ebener et al 2006). Previous studies have shown that the incorporation of knowledge structures into educational games could effectively enhance students' achievement without affecting their motivation and self-efficacy (Chu et al 2015). For this reason, this study attempted to visualize the structure of knowledge in an educational game.…”
Section: Digital Educational Games For Mathematics Learningmentioning
confidence: 99%
“…Researchers have found that flow is positively related to children's learning performance and motivation for continuous learning (Cheng et al, 2021). Besides, flow associates with children's divergent thinking which benefits their creative problem-solving abilities (Chu et al, 2015). Many studies have highlighted the importance of challenge-skill balance to promote children's flow experience (Perttula et al, 2017).…”
Section: Alternate Reality Gamesmentioning
confidence: 99%
“…Concept mapping supports children to connect relevant concepts and realise abstract concepts in knowledge construction, which enhances information organisation and memory to improve learning efficiency (Wang et al, 2016). Previous research showed that ARGs which incorporate the concept mapping approach can improve children's learning performance more than the conventional game approach (Chu et al, 2015). With mobile concept mapping-based approaches in ARGs, children can share and synthesise different thoughts from others to improve their collective efficacy (Lin et al, 2016).…”
Section: Concept Mappingmentioning
confidence: 99%
See 1 more Smart Citation
“…Therefore, its application in education increases students' sense of participation and supports effective learning (Shih et al, 2010). As the RPG background can be set in ancient times or in foreign countries, it has been applied in learning activities related to history (Chua, Yang, & Chen, 2015) and foreign languages (Cornillie, Clarebout, & Desmet, 2012). Compared with other types of games, the requirement in RPGs to complete certain tasks in order to advance to the next level effectively enables students to acquire problemsolving abilities (Liu et al, 2014).…”
Section: Introductionmentioning
confidence: 99%